SHE’S TWELVE AND SHE CAN’T WRITE:AN ACTION RESEARCH EXPLORATION TO MEDIATE SPECIAL EDUCATIONAL NEEDS PUPIL TO LEARN TO WRITE (Practitioner Research, 2019)
School’s daily tasks typically require pupils to write their own names. However, for some special educational needs (SEN) pupils, the task of writing name is tough for them and it requires the teacher to impart the specific skills for the pupils. This action research investigated an intervention that was employed by the first author, who is a special education teacher, to assist a Down syndrome pupil in writing the letter “H” in her name legibly as well as to discover materials and resources that could be used to facilitate the intervention processes. The action research intervention was conducted in a Special Education Integrated Programme classroom of a primary school in the northern region of Malaysia. The research participant was a 12-year old female Down syndrome pupil. By adopting Vygotsky’s notion of zone of proximal development and information-processing theory, a four-step intervention strategy involving fine motor warm-up, letter introduction, guided practice and paper-pencil practice was devised to facilitate the pupil’s writing attempts. Writing samples were collected and analysed based on existing writing marking criteria which were adapted for the purpose of this study. Reflective journals were kept throughout the intervention period for continuous improvement purposes. The pupil was able to write the letter “H” legibly based on the four-step intervention strategy. The materials and resources used during the intervention were mainly derived from available resources in the classroom and were economically viable for the teacher to construct. Reflections on the intervention process suggested that the teaching and learning of pupils with SEN were more interesting and meaningful when the intervention involved the application of learning theories together with the use of teaching strategies that were incorporated multi-sensory approach. The findings can serve as guidelines for special education teachers to overcome difficulties of Down syndrome pupils in name writing. Meanwhile, reflections from the process can serve to enlighten the current literature on facilitating handwriting skills among pupils with SEN.